Dualism of Positive Law and Islamic Law in Indonesia: Law Enforcement for Lesbian, Gay, Bisexual and Transgender Communities - Ita Fitriana; R Rizka; Nada Ferika Trihandayani; Etrico Adyatama (Urecol Journal. Part H: Social, Art, and Humanities, 2021)
Human rights must be implemented by the rules of community life, where each community group has its view and application of the freedom of human rights. The enforcement of human rights for LGBT people with Islamic law in Aceh is opposed by the international community because it is considered a violation of human rights. So the urgency of this research is to find out how far a person's understanding of human rights freedom is and what is the foundation on which they base human rights to exercise. After that, it will be concluded whether religious values continue to dominate society in acting. This study uses a descriptive-analytical method with a normative juridical approach, where the data and information to be collected both in terms of assessment and in terms of management is carried out interdisciplinary and multidisciplinary as well as cross-sectoral. The data and information are then analyzed in-depth normative juridical so that an overview of human rights in Indonesia is obtained. The results show that the concept of human rights applied in Indonesia uses the concept of cultural relativity and will not be relevant if it uses the concept of human rights in western countries which emphasize individual freedom.